(untitled) (Altre Modernità, 2010)
Social rites attempt to fill in the bodily gaps left by death. The aesthetic rituals of the novels Das Parfum (1985) by Patrick Süskind and Oceano mare (1993) by Alessandro Baricco come to terms with death in representations of murder which convey a relativist conception of being as presence, based on creative and critical dissent from the social resentment revolving around the dualist consent of life as absolute essence and death as absence. Both novels present death in ways which dissent from the resentful mourning conventions derived from the consensual distinction between life and death. An interdisciplinary approach, where philosophical perspectivism and post-structuralism, sociological intersectionality, and historical hybridity are integrated, suits to the intercultural analysis of the intertextual relations between these literary works. Their metaphors of dissenting serial murders and murderous social resentment converge in aesthetic rituals which celebrate the cycle of being in death.